FORENSIC ANALYSIS OF BLUNT TRAUMA IN ORAL CAVITY THAT CAUSE THE DEATH: A REVIEW - Langit, Ken Sekar; Auerkari, Elza Ibrahim (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2021)
Traumatology is one of the pathology forensic studies to analyze the injury, effect and its relation to the cases of violence of criminals. According to the etiology, its division into four major types of trauma, there are blunt trauma, sharp trauma, gunshot wound, and others. Blunt trauma is a common case in forensic and often becomes the cause of death in many cases, such as accident, homicide, and murderer. Blunt trauma in the oral cavity also can cause death by various mechanisms such as infection, bleeding, and asphyxia. Keyword: blunt trauma, oral cavity, cause of death